Acute effect of complexity in basketball on cognitive capacity - Gutiérrez-Capote, Alejandro; Madinabeitia, Iker; Alarcón, Francisco; Torre, Elisa; Jiménez-Martínez, Jesús; Cárdenas, David (Frontiers in Psychology, 2024)
Background Executive functions, notably inhibition, significantly influence decision-making and behavioral regulation in team sports. However, more research must be conducted on individual player characteristics such as experience and motor skills. This study assessed how accumulated practical experience moderates inhibition in response to varying task difficulty levels. Methods Forty-four university students (age: 20.36 ± 3.13 years) participated in this study with two sessions: one followed standard 1 × 1 basketball rules (“Regular Practice”), while the other imposed motor, temporal, and spatial restrictions (“Restriction Practice”). Functional difficulty was controlled by grouping pairs with similar skill levels. Flanker and Go-Nogo tasks were used. Results Increasing complexity worsened cognitive performance (inhibition). “Restriction Practice” showed a significantly slower and less accurate performance in both tests than “Regular Practice” (p < 0.001). Experience positively impacted test speed and accuracy (p < 0.001). Conclusion In sports, acute cognitive impacts are intrinsically linked to the task’s complexity and the athlete’s cognitive resources. In this sense, it is essential to adjust individually the cognitive demands of the tasks, considering each athlete’s specific cognitive abilities and capacities.